Flood risk and mitigation calculator tool to support decision-making for enhancing community resilience: a case study of the U.S.A. Gulf Coastal region - Mostafiz, Rubayet Bin; Al Assi, Ayat; Taghinezhad, Arash; Friedland, Carol J.; Rohli, Robert V.; Rahim, Md Adilur; Emrich, Christopher T.; Gall, Melanie; Johnson, Eric (Frontiers in Built Environment, 2025)
Real-estate websites make it easy to find and access information about a home. Information on property value, square footage, number of rooms, quality of schools, crime rates, and more is readily available. Some of these platforms have begun integrating climate-related risks in generic ways. However, this information provides limited if any actionable value and is unlikely to guide people’s decision-making on buying or renting a home, deciding where to vacation, or investing in a property. Making residents aware of the natural hazard risks to which their homes may be exposed is an important component of making communities more resilient. Both a need and an opportunity exists to communicate hazard risk at the address-level in a meaningful and actionable way that goes beyond hazard probabilities and historic losses. One such example is the Flood Risk and Mitigation Calculator (FRAMC) embedded within the “HazardAware” platform, which educates users on the resilience of their community, neighborhood, and perhaps most importantly, their home (present or future, temporary or permanent). FRAMC enables users to assess their local flood risk, explore risk reduction options, and determine the financial viability of implementing potential risk mitigation options. This study outlines the development of the FRAMC and its integration into the larger framework of HazardAware. FRAMC’s key features include a user-friendly interface and draw on novel research related to innovative mitigation strategies. The intent of FRAMC is to enhance users’ ability to make informed decisions, take proactive measures in mitigating flood hazards, and contribute to the development of resilient, residential communities.